2022
DOI: 10.3389/fphar.2022.814370
|View full text |Cite
|
Sign up to set email alerts
|

Alpinetin: A Review of Its Pharmacology and Pharmacokinetics

Abstract: Flavonoids isolated from medicinal herbs have been utilized as valuable health-care agents due to their virous biological applications. Alpinetin is a natural flavonoid that emerges in many widely used medicinal plants, and has been frequently applied in Chinese patent drugs. Accumulated evidence has demonstrated that alpinetin possesses a broad range of pharmacological activities such as antitumor, antiinflammation, hepatoprotective, cardiovascular protective, lung protective, antibacterial, antiviral, neurop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 180 publications
0
20
0
Order By: Relevance
“…This natural flavonoid has also been reported to exist in Polygonatum ferruginea [ 38 ]. Alpinetin is one of the major active compounds of Chinese patent drugs such as Jianweizhitong tablet, Fufangcaodoukou tincture, Baikoutiaozhong pill, and Xingqiwenzhong granule [ 39 ]. Recently, Zhao et al [ 39 ] systematically reviewed the pharmacological activities of alpinetin, including the counteraction against cardiovascular disease, inflammatory diseases, carcinoma, bacterial and virus infection, and neuro-disorders.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This natural flavonoid has also been reported to exist in Polygonatum ferruginea [ 38 ]. Alpinetin is one of the major active compounds of Chinese patent drugs such as Jianweizhitong tablet, Fufangcaodoukou tincture, Baikoutiaozhong pill, and Xingqiwenzhong granule [ 39 ]. Recently, Zhao et al [ 39 ] systematically reviewed the pharmacological activities of alpinetin, including the counteraction against cardiovascular disease, inflammatory diseases, carcinoma, bacterial and virus infection, and neuro-disorders.…”
Section: Resultsmentioning
confidence: 99%
“…Alpinetin is one of the major active compounds of Chinese patent drugs such as Jianweizhitong tablet, Fufangcaodoukou tincture, Baikoutiaozhong pill, and Xingqiwenzhong granule [ 39 ]. Recently, Zhao et al [ 39 ] systematically reviewed the pharmacological activities of alpinetin, including the counteraction against cardiovascular disease, inflammatory diseases, carcinoma, bacterial and virus infection, and neuro-disorders. Regarding grandisin, it is a tetrahydrofuran neolignan, isolated from Piper solmsianum [ 40 ], and Virola surinamensis [ 41 ], with the pharmacological activities of antinociception and anti-inflammation [ 41 ].…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have shown that CAR and ALP have antibacterial activity, 22,33 and we wondered about the antibacterial activity of CAR/ALP after trapping ACR. Therefore, we investigated the antibacterial activity of the adducts.…”
Section: Anti-bacterial Activity Of Car Alp Car-acr-1 Car-acr-2 and A...mentioning
confidence: 98%
“…Simultaneous activation of AhR transcription factors, by upregulating cytochromeP4501A1 levels, increases Foxp3 expression, causes Treg cells differentiation, and comprehensively regulates 17/Treg balance through these two pathways [53][54][55]. Alpinetin is a flavonoid isolated from Alpinia officinarum Hance, which has hepatoprotective, cardiovascular, antibacterial, antiviral, and neuroprotective effects and is widely used in medicine [56,57]. Studies have confirmed that Alpinetin promotes Treg cells differentiation and restores 17/Treg balance by activating AhR, promoting miR-302 expression, while downregulating DNA methyltransferase-1 expression, reducing Foxp3 promoter region methylation levels, promoting cAMP-response element binding protein binding to Foxp3 promoter region, and upregulating Foxp3 expression, further improving intestinal mucosal pathological outcomes in colitic mice, including alleviating surface epithelial damage and significantly reducing crypt number and inflammatory cell infiltration [58].…”
Section: Chinese Herbal Monomers and Eir Extracts Prevent Andmentioning
confidence: 99%